Women in Cleveland An Illustrated History - Morton, Marion (Indiana University Press, 1995)
It has been one hundred years since a formal work was published on the role of women in the history of the city of Cleveland. This book adds to the early pioneering work, Memorial to the Pioneer Women of the Western Reserve. In addition, over 200 fascinating historical photographs have been reproduced, some to illustrate the text, and the rest in a series of photographic essays covering the following topics: Growing Up, Sports and Recreation, Marriage and the Family, Work, Fashion, Clubs and Associations, and Growing Old.